Nonpoint Source Pollution From a Tropical Urban Residential Area - Al-Mamun, Abdullah (2005)
Despite all efforts taken by the Government, water quality related problems in Malaysian rivers remain unresolved. This is mainly due to the fact that most of the attention is focused on the point source (PS) pollutions whereas a significant amount of annual pollution load is also generated from the nonpoint sources (NPS) as a result of storm runoff. After the endorsement of the urban stormwater management manual by the cabinet in June 2000, it was realised that in order to quantify the significance of NPS pollution there was an urgent need to conduct detail studies on the storm runoff quality from various landuses in Malaysia. As such, this pioneer study was conducted in detail to characterise the storm runoff quality from a developed urban residential area. Rainfall is the main driving force of nonpoint source pollution. Therefore, the daily rainfall data was collected from a nearby station to study the distribution of daily rainfall from 1985 to 2003. It was found that about 83% of the storm events was less than or equal to 25 mm. This proved that the most frequent and small rainfall events were responsible for more NPS pollution. This finding was in agreement with the hypothesis that frequent rainfall events cause more NPS pollution. Frequency analysis of monthly maximum rainfall revealed that rainfall amount of 3-month return period for the NPS pollution control would be 60 rnm. FiRy-six rain events were monitored to calculate the event mean concentration (EMC) values of the parameters, which are contributed mostly from the nonpoint pollution sources. The median EMC values for Turbidity, TDS, TSS, BOD, COD, Pb, Zn, Cu and Cr were calculated to be 36 NTU, 47.3, 126.5,29, 120, 0.0143, 0.3046, 0.0135 and 0.0187 mg/L, respectively. These data can be used to calculate the annual pollution loading from an urban residential area with combined sewerage system, which conveys sullage and storm runoff.It was determined that TSS (78.4%), COD (51.8%), Pb (loo%), Zn (80%), Cr (100%) and Cu (52.7%) were mostly generated from the nonpoint pollution sources. This finding was in agreement with the second hypothesis that nonpoint sources contributed more annual TSS, COD and heavy metal loads than point sources in a developed urban residential area. Compared to the point sources,lesser amounts of BOD and TDS loadings were generated from the nonpoint sources, which were 39.1% and 20%, respectively. However, according to the existing water quality guideline, contribution of BOD loading from runoff was considered significant. The hypothesis was not true in the case of BOD and TDS annual loading, which were more generated from the point sources.